Effectiveness of an educational training program on skin reactions induced by immunotherapies, Epidermal Growth Factor Inhibitors (EGFRI) treatments, and chemotherapies: A pilot study - Papoui, Eleni (My University, 2023)
Pruritus, rash, and photosensitivity are among the most prevalent skin reactions observed to individuals undertaking immunotherapies, Epidermal Growth Factor Receptor Inhibitor (EGFRI) treatments and chemotherapies. The incidence of immunotherapy-induced pruritus to this group ranges from 3.0% to 30.7%, while skin rash occurs in 50–100% of patients treated with EGFRI. In the same pattern, the percentage of skin photosensitivity ranges from 22.2% to 66.7% in patients treated with chemotherapeutic drugs. These three types of skin reactions, have both a physical and a psychological impact on the patients, affect their Quality of Life (QoL) and in severe cases can lead to either a treatment dose reduction or delay in treatment dose optimization or even discontinuation of cancer treatment.
Keywords: rash; photosensitivity; pruritus; educational; chemotherapy; EGFRI; immunotherapy